The effect of mobile device usage on creating text reviews - Park, Keeyeon; Kim, Hye-Jin; Kim, Jong Min (Asia Pacific journal of marketing and logistics, 2023)
PurposeThe purpose of this study is to examine how the usage of mobile devices influences text-posting behavior in the online review-generation process. This study attempts to improve the understanding of the negative impacts of mobile channels on the quality of online reviews.Design/methodology/approachThe authors develop a series of hypotheses to investigate the text-posting behaviors with mobile device usage. To examine the authors' hypotheses, the authors collect online reviews posted in London hotels on Booking.com. The authors first use a logistic regression model to examine the relationship between the usage of mobile devices and text-posting behavior. Then, the authors explored the characteristics of textual content in mobile reviews compared to reviews written via traditional devices.FindingsThe authors' finding shows that the use of mobile devices negatively influences text-posting behavior. Compared to traditional devices, consumers are less likely to post texts in their reviews with mobile devices. Although consumers decide to post text comments in consumers' reviews, the quality of textual content is relatively low – short in length, with limited analytical thinking and less authenticity.Originality/valueTo the best of the authors' knowledge, no study has attempted to explore text generation in review-posting behaviors in the context of mobile channels. Also, the authors' findings show the negative effects of using mobile channels on the value of generated information, which is counterintuitive to previous research.